An investigation on behavior of RC frames with non-interacting infill wall. (15th October 2021) - Bikçe, M.; Emsen, E.; Erdem, M.M.; Bayrak, O.F.
Highlights: In-plane behavior of the frame with non-interacting infill was studied experimentally. Behavior of the frame with non-interacting infill compared with bare and fully infilled frames. The non-interacting wall got minor damage even in extreme displacements. In-plane behavior was improved. Numerical FE models were validated by the experimental behavior. Abstract: Infill walls, which are generally assumed as dead loads in building design, affect the lateral resistance, stiffness, and energy consumption of the frames. Investigations conducted after earthquakes show that the infill walls, whose effects are neglected in the design, can change the earthquake behavior of the structure and cause unforeseen damages in the buildings and even collapses in some cases. In order to match the behavior of designed and built frames, the technique of isolating the infill wall from the RC frame with non-interacting infill was adopted. In this study, in-plane behavior of bare, traditionally infilled frames and a frame with non-interacting infill wall were investigated experimentally under reversed cycling loads, then their numerical models were calibrated. As a result, in contrast to the traditionally infilled frame, it has been seen that the frame with non-interacting infill behaves close to the bare frame in the initial drifts and maintains its lateral resistance without a damage until further drifts. Therefore, it has been found that constructing the infill wall with non-interacting joint improves the in-plane behavior.